Susceptibility among populations of crabgrass to herbicides inhibiting photosystem II - Lucio, F. R.; Barroso, A. A.M. [UNESP]; Toledo, R. E.B.; Pitelli, R. A.; Victoria Filho, R. (FapUNIFESP (SciELO), 2018)
Weed interference reduces the productive potential of crops. Among the control methods used, chemical ones occupy a major position. The repeated application of the same mechanism of action selects tolerant plants. Among the species that affect sugarcane, crabgrass is one of them. This study has aimed to know the tolerance of different populations of this species to herbicides inhibiting photosystem II. Three populations were collected, identified and submitted to the application of ametryn and diuron herbicides in ten different doses, and the experiment was conducted in a experimental design of complete randomized blocks with four repetitions in a factorial arrangement of 10 x 3 (10 doses x 3 populations), being one trial for each herbicide. Sixty days after application, visual control and plants shoot dry biomass were evaluated. The data were submitted to an analysis of variance by the F test and, when significant, their means were compared using the Tukey’s test. The averages related to the herbicide doses were submitted to a graphical analysis by applying a log-logistic regression where the herbicide doses required to cause 50 or 80% of injury and reduction of dry biomass of plants were calculated. The resistance factor was calculated to determine the difference in herbicide tolerance among populations. Based on the results, it was observed that the populations exhibit differential sensitivities to herbicides and the one originated in Brazilian city Ribeirão Preto was resistant to ametryn. The population originated in Brazilian city Santa Cruz das Posses was less sensitive to diuron. The RF values ranged between 1.0 and 2.34.
Suscetibilidade entre Populações de Capim-Colchão a Herbicidas Inibidores do Fotossistema II
Keywords: Ametryn; Digitaria horizontalis; Diuron; Resistance; Tolerance